EFEK PENGEMBANGAN KARYAWAN DAN PENEMPATAN KERJA KARYAWAN TERHADAP EFISIENSI KERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. MODERN INDUSTRIAL ESTATEE - CIKANDE - Ade Fauji; Muhammad Fikri (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
The development of a company is due to factors from employees, the company tries to achieve appropriate work efficiency, the achievement of work efficiency is seen based on what kind of employee development occurs what is the development of employees who work efficiently, the creation of work efficiency is also seen from how the company places employees in positions that are in accordance with what employees have. In order to achieve work efficiency based on employee development and work placement, work discipline is a connecting factor to improve work efficiency values ​​for the better. This study aims to determine the effect of employee development and work placement on work efficiency through work discipline as an intervening variable at PT. Modern Industrial Estate either directly or indirectly. The research method uses a quantitative approach with data in the form of primary and secondary data, the sample used is 72 employees. Based on the results of hypothesis testing directly and indirectly there is an effect of employee development on work efficiency through work discipline and the effect of employee work placement on work efficiency through work discipline At PT. Modern Industrial Estate. So it can be concluded that work discipline can be an intervening variable in the indirect relationship between employee development and work placement on work efficiency